Green Finance and Investment Mapping Channels to Mobilise Institutional Investment in Sustainable Energy. - Publishing, OECD (OECD Publishing, 2015)
What are the channels for investment in sustainable energy infrastructure by institutional investors (e.g. pension funds, insurance companies and sovereign wealth funds) and what factors influence investment decisions? What key policy levers and risk mitigants can governments use to facilitate these types of investments? What emerging channels (such as green bonds, YieldCos and direct project investment) hold significant promise for scaling up institutional investment?. This report develops a framework that classifies investments according to different types of financing instruments and invest.